The European Union and China, 1949-2008 [ basic documents and commentary - Snyder, Francis G. (Oxford Portland, Or. : Hart, 2009)
A comprehensive reference book and commentary on basic documents about relations between the EU and the People's Republic of China from 1949 onwards. It contains various significant official and unofficial documents in English and Chinese about EU-China relations since the founding of the PRC in 1949
1. Diplomatic Relations, 1949-1975: From New China and New Europe to Diplomatic Relations between China and the EEC INTRODUCTION FIRST GENERATION, 1949 SECOND GENERATION, 1950 THIRD GENERATION, 1954-1964 FOURTH GENERATION, 1970-1979 EEC-CHINA RELATIONS, 1975 -- CONCLUSION 2 Bilateral Agreements on Trade and Textiles, 1975-Present: From the Establishment of Diplomatic Relations through Chinese Accession to the World Trade Organization INTRODUCTION TRADE AGREEMENTS TEXTILES AGREEMENTS -- 3 Policy Papers and Related Documents, 1995-Present: From Trade to Strategic Partnership INTRODUCTION EXPLORATION AND CONSTRUCTION, 1995-2003 DEEPENING AND MATURING, 2003-2006 MANAGING PARTNERSHIP AND COMPETITION, 2006 AND BEYOND -- 4. Political Dialogues, 1994-Present: Summits, Human Rights and Arms INTRODUCTION SUMMITS POLICY DIALOGUES -- 5. Sectoral Dialogues, Joint Declarations and Memoranda of Understanding, 1990-Present INTRODUCTION HIGH LEVEL MECHANISM (HLM) SECTORAL DIALOGUES CONCLUSION -- 6. Bilateral Agreements other than Trade and Textiles, 1994-Present INTRODUCTION LEGALLY BINDING AGREEMENTS BETWEEN THE EC AND CHINA -- 7. Cooperation Projects, 1985-Present 8 Relations between the EU and Hong Kong and Macao, 1989-Present INTRODUCTION HONG KONG MACAO 9 EU, China and the World Trade Organization INTRODUCTION
Description based on print version record
Includes bibliographical references and index
Keywords: China -- Foreign relations -- European Union countries -- Sources; European Union countries -- Foreign relations -- China -- Sources